Effectiveness of Various Maintenance Therapy in Ovarian Cancer A Scoping Review - Bawono, Mada Ilham; Mufidah, Belinda (Universitas Malahayati, 2025)
ABSTRACT Ovarian cancer is highly lethal with a lifetime risk of up to 1.1%. Despite advances in treatment like cytoreductive surgery and chemotherapy, high recurrence rates challenge disease management. Maintenance therapy is crucial for extending progression-free survival (PFS) and delaying recurrence. This study aims to evaluate the effectiveness of various maintenance therapies published in the last 10 years, focusing on PARP inhibitors, angiogenesis inhibitors, monoclonal antibodies, and combination therapies. A scoping review was conducted following the PRISMA ScR Protocol. The search was conducted in PubMed, ScienceDirect, and Springer databases. After removing duplicates and applying inclusion and exclusion criteria, 208 articles were screened and 22 articles were selected for final review and critically appraised using the Cochrane RoB 2 tool. This review found that maintenance treatment with PARP inhibitors (e.g., olaparib, niraparib, rucaparib) showed significant improvements in PFS, especially in patients with BRCA mutations and homologous recombination deficiency (HRD). Combination therapies, such as olaparib with bevacizumab, also enhanced PFS. Angiogenesis inhibitors like pazopanib showed variable effectiveness, while monoclonal antibodies like gatipotuzumab had limited success. The combination of pegylated liposomal doxorubicin (PLD) with carboplatin showed potential in improving PFS. These findings highlight the effectiveness of personalized maintenance therapies in extending PFS in ovarian cancer patients. Keywords: Ovarian Cancer, Maintenance Therapy